Analysis of Factors Affecting the Quality of Calculation of State Financial Losses Sued in Court - Suryadewi, Dwiyoga; Martani, Dwi (E-Jurnal Akuntansi, 2025)
The results of the calculation of state losses have received many lawsuits related to aspects of calculation methods, authority, and audit processes. This study aims to analyze the factors that influence the quality of the results of the calculation of state losses that are sued in court. A qualitative approach is used in this study, with data analysis techniques using thematic analysis and content analysis . Primary data comes from interviews and secondary data comes from the results of analysis of case decision documents on the website of the Supreme Court of the Republic of Indonesia. The results of the study indicate that the factors that influence the aspect of the calculation method are (1) differences in perception in choosing a calculation method, (2) data reliability, and (3) data acquisition and analysis techniques. From the aspect of authority, there are (1) differences in hierarchy and (2) interpretation of laws and regulations. Meanwhile, from the aspect of the audit process, there are (1) differences in interpretation of audit implementation standards, (2) data acquisition and analysis techniques, (3) credibility, independence, and calculation results of other experts, (4) competence and experience of the audit team, and (5) reliability of the results of the initial presentation/review. Keywords: Calculating State Losses; Calculation Methods; Authorities; and the Audit Process.